The North-South Wage Differential - Gallaway, Lowell E. (The Review of Economics and Statistics, 1963)
highly abstracted purely competitive model A of a factor market has as an end result an equalization of factor prices throughout the market. Consequently, the persistence of sizeable regional wage differentials in a national labor market calls for an explanation. An often offered one is that there are barriers to the free flow of resources between regions, barriers such as a lack of labor mobility, high moving costs, lack of labor market information, etc. Such an explanation is suggested by Cairnes' concept of non-competing groups 1 and receives support from the findings of the labor market research of Reynolds, Kerr, et al.2 However, explaining regional wage differentials by such a device is not entirely satisfactory. To a sizeable extent this approach is a question-begging one. While it provides considerable insight into the factors which serve to perpetuate a wage differential, it does not afford much that is helpful with respect to determining the forces which generated the initial differential. After all, the existence of regional wage differentials insistently demands an explanation primarily because it represents a deviation from the expected result of a competitive market. Explaining such a differential by merely pointing out that the market is imperfect is next to no explanation at all. This is tautologically implicit in the conceptualization of the competitive market. If a competitive market eliminates differentials and differentials persist, then the market is obviously not competitive and barriers to the adjustment process must exist in order to perpetuate the differentials. This suggests that an appropriate point of departure for attempting to explain the existence of regional wage differentials is to accept as a working proposition the assumption that barriers to the free flow of resources between regions do exist. Given this, the task of accounting for regional wage differentials becomes one of determining what forces work to create differentials. Several alternative explanations may be considered. Trade union representatives would argue that regional wage differentials are created by the ability of employers to exploit an unorganized labor force. Others have suggested that an explanation may be found in a more plentiful labor supply or a deficiency of product demand 3 while a fourth possibility is that the production functions vary interregionally so as to produce a lower marginal value product schedule for the workers of one of the regions. In this paper an attempt will be made to shed some light on the nature of regional wage differentials by developing suitable empirical tests for several of the suggested explanations of their causes. As a vehicle for discussion, the best known of the regional wage differentials, the North-South one, will be treated.